Calcium and sodium as regulators of the recovery of four Daphnia species along a gradient of metal and base cations in metal contaminated lakes in Sudbury, Ontario, Canada - Martha Patricia Celis-Salgado; Wendel (Bill) Keller; Norman D. Yan (Journal of Limnology, 2016)
Smelting of sulphur-rich metallic ores in Sudbury, Ontario, Canada, has caused acidification and metal contamination of thousands of lakes in the region. Recent reductions in smelter emissions have resulted in much ecological recovery, but the recovery of Daphnia species has been poor. To determine if Cu and Ni toxicity could explain differences in daphniid recovery among lakes, we compared results of 14 d static with renewal bioassays in waters from Blue Chalk Lake, an uncontaminated reference lake 200 km from Sudbury, and from five Sudbury lakes ranging in distance from the smelters and varying in metal and cation concentrations. We spiked Blue Chalk Lake water with Cu and Ni to levels resembling those of the Sudbury lakes and also tested the lake waters for toxicity. Survival of Daphnia pulex, D. pulicaria and D. mendotae decreased monotonically with increasing metal concentrations in the spiked Blue Chalk Lake treatments, falling from 90% in the controls to 0% at the two highest Cu and Ni levels, reflecting levels of Middle and Hannah lakes. In contrast, survival in waters collected from the actual Sudbury lakes did not monotonically track their total metal concentrations. Rather, survival fell to 0% in Clearwater Lake water, a lake with intermediate metal contamination (8.9 and 79.9 μg L–1 of Cu and Ni, respectively) vs 70-100% in the other lakes. We performed an additional assay with Clearwater Lake waters increasing its Ca and Na concentrations, singly and in combination to levels that reflected the levels in Middle Lake. The survival of the four daphniid species increased from 0% up to 80-100% with added Ca and from 0% to 60-90% with added Na. Lipid-ovarian indices had a similar trend to survival for D. mendotae and D. pulicaria in Bioassay 1, varying with the cation concentrations in the lakes for the daphniids in Bioassay 2. The bioassays results imply that regional recovery patterns of daphniids in Sudbury lakes cannot be understood without as a minimum considering both metal and base cation concentration differences among lakes, and give an indication of differences among Daphnia species to cope with metal stress.